Pembuatan Video Promosi dengan Metode Value Proposition Canvas pada Hompimpaa.id - Fiby Nur Afiana (Universitas Amikom Purwokerto, 2021)
Hompimpaa is one of the startups that is growing by focusing on early childhood education with the development of interests and talents. The obstacle faced by Hompimpaa is that it is not widely known by the public, consumers are limited to parents who follow parenting communities. Promotional media also has not maximally benefited hompimpaa. The Value Proposition Canvas (VPC) method as one of the strategies to analyze needs, the results of promotional media design with Value Proposition Canvas Analysis show that the main problem or pain faced by consumers is that the user/consumer has not fully mastered the platform provided by Hompimpaa. With the right analysis, a promotional video can be designed that is able to answer market needs, especially parents who want to hone their early childhood interests and talents through the right parenting and child application, namely through Hompimpaa. Through the resulting promotional video, it is hoped that it will introduce hompimpaa to a wider market share.